Job satisfaction and organizational commitment: a study on Malaysian employees in manufacturing and service firms / Roselindawati Zainal Abidin - Zainal Abidin, Roselindawati (Faculty of Business and Management, 2008)
The purpose of this study is to gain a better understanding of the relationships between job satisfaction and organizational commitment of employees at manufacturing sectors and service firms in Johor, Melaka and Selangor. Elements from Job Descriptive Index such as pay, promotion, the work itself, supervision and co-workers have been studied whether or not these factors have correlation and relationship with job satisfaction and organizational commitment. The study generated a 90 percent response rate from 90 employees who had worked at these manufacturing and service sectors. Out of 100 questionnaires that have been distributed, only 90 questionnaires were returned. The data obtained for this study are by using primary data and secondary data. Respondents were required to answer the questionnaires that contain elements that potentially have relationship with job satisfaction and organizational commitment. Data are analyzed by using Reliability Test, Pearson Correlation Analysis, Cross Tabulation, Frequency Analysis and Descriptive statistics through SPSS Program. The results shows that all of the variables under job satisfaction have relationship with organizational commitment.